ANALISIS PENGARUH TINGKAT PDRB PERKAPITA, INDEKS PEMBANGUNAN MANUSIA, DAN PENANAMAN MODAL ASING TERHADAP KETIMPANGAN PENDAPATAN DI INDONESIA PERIODE TAHUN 2019-2021 - Miftahul Janah (UNIVERSITAS MARITIM AMNI SEMARANG, 2022)
Income inequality is one aspect of poverty that needs attention because it is essentially a measure of relative poverty, namely calculating poverty as part of the regional income distribution. Good economic development can be seen from the level of gross regional domestic product per capita (PDRBPKP), Human Development Index (IPM) and Foreign Investment (PMA) in various regions in Indonesia. Changes in each of these variables are influenced by income inequality in various regions. regions, especially in Indonesia. The purpose of this study is to analyze the Gini ratio (income inequality) and the factors that influence it in Indonesia for the 2019-2021 period. This research is a quantitative research. The variables used in this study are Gini ratio, GRDP per capita, Human Development Index, and Foreign Investment. The panel data method is used as an analysis in the form of cross section data from 34 provinces in Indonesia and time series data for 2019-2021. The results of this study indicate that PDRBPKP has a negative effect on income inequality, HDI has a positive effect on income inequality, and FDI has a negative effect on income inequality in Indonesia for the 2019-2021 period.